Influence of Board Traits and Audit Committee Characteristics on Firm Profitability: Study of Oman’s Listed Companies: Impact of Board Traits and Audit Committee Characteristics on Firm Profitability in Oman (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of the study is to investigate Influence of Board traits and Audit Committee Characteristics on firm profitability. The study has analyzed twenty financial sector companies listed on the Muscat Securities market, it has further segmented the financial sector in two segments banking sector and non-banking sector. Seventy Observations over a period of ten years have been analyzed for banking sector companies, one hundred and twenty-seven observations for similar period have been analyzed for non-banking companies.Profitability is the main dependent variable as part of this study. Profitability is arrived by taking the average of return on equity and assets. Board Size[bs] Board Independence[ind] Audit Committee Size[acs] and Audit Committee meetings[nacm] are taken as independent variables taken as part of the study. In case of non-banking firms, no relation was found between profitability of the firm and various independent variables taken as part of the study except number of audit committee meetings. On the contrary in case of banking sector firms all independent variables as part of corporate governance mechanisms showed a relationship with profitability of the firm.This is research-based paper and its contribution to the academic literature to Oman is of great value addition to the scarce literature available on the same topic. Different stakeholders can benefit from the findings and would facilitate their decision making in implementing new policies and strategies.